Teachers’ Challenges in Teaching Reading to Students with Low English Proficiency at Telkom Schools Medan - Gultom, Ika Marlina; Tarigan, Sri Ninta; Br Sembiring, Elita Modesta (English Language Teaching Prima Journal (ELT), 2025)
This study examines the difficulties faced by English teachers at Telkom Schools Medan when instructing reading to students who don't speak the language well. Using a qualitative case study methodology, information was gathered via document analysis, classroom observations, and interviews. Limited student vocabulary, poor comprehension of narrative text structure, inference difficulties, low motivation, and a lack of instructional resources are the five main issues identified by the findings. These issues make it difficult for teachers to provide effective instruction and impair students' reading comprehension. Teachers employ techniques like scaffolding, differentiated instruction, and the use of multimodal materials in spite of the obstacles. However, the lack of institutional support frequently limits their efforts. In order to promote reading development in EFL contexts, the study emphasises the necessity of enhanced teacher preparation, enriched learning materials, and greater institutional cooperation.